La pratique dédicatoire du dramaturge Pierre du Ryer : vers un « lieu vide du pouvoir » ? - Tiphaine Pocquet (Les Dossiers du GRIHL)
Dedication letters prior to Pierre du Ryer’s plays meet with an interesting development. The author chooses protectors that are powerful but also dissenters, like César de Vendôme. Eventually, he gives up dedication. There is one pivotal preface in his work: the dedication letter of his tragedy Saul, addressed to « nobody », that is to say to « everybody », in 1642. We aim at understanding such practice by starting with the studying of the political circumstances that surround the author’s stance. It seems power has moved away from the fading “unique authority” (that of the traditional dedicator and, behind him or her, the protective king or chosen lord) to be lodged into the hands of a public of readers that is at the same time unique and plural. Thus, the dedication letter becomes an empty place of power, with edges perpetually redefined.